Africa on the road to industrial progress - Interview: Li Yong, Director-General of the United Nations Industrial Development Organization (UNIDO). - Kingsley Ighobor (Africa Renewal, 2017)
As the director general of the United Nations Industrial Development Organization (UNIDO), Li Yong leads a specialised agency that promotes industrial development, inclusive globalization and environmental sustainability. Recently in New York, Mr. Yong took part in a special meeting on “innovation in infrastructure development and sustainable industrialization” in developing countries and countries with special needs. He spoke with Africa Renewal’s Kingsley Ighobor on a range of issues pertaining to Africa’s industrialization. Here are the excerpts: